Islamic Values Identification in the Conversion of Cultural Heritage Buildings in Malang City Case Study: The Shalimar Boutique Hotel and Lafayette Coffee and Eatery - Setiono, Arief Rakhman; Bisri, Muhammad; Djakfar, Ludfi; Hasyim, Abdul Wahid; Sholihah, Rafidatus; Damayanti, Fifka Amalia (Journal of Islamic Architecture, 2025)
Islamic values encompass important principles and teachings that guide individuals on how to live their lives in this world. Islamic teachings provide guidelines as a basis for decision-making, which is considered an act of worship to Allah SWT. Heritage buildings are crucial for reflecting a society's history and the development of a city. In Indonesia, particularly in Malang City, known as the city with the best colonial planning in the Indies, preserving heritage buildings is vital to preserving their historical, scientific, and cultural values. One way to maintain these buildings is through conversion, which involves changing their functions to meet the needs of a growing city. Since Malang's majority of the population are Muslims who adhere to the principles of Islamic values as their main guide in life, converting buildings should be viewed as an act of worship and align with Islamic teachings. This study aims to identify Islamic values in the conversion of heritage buildings in Malang City and understand how these values can be applied so that the buildings are well-used and managed by the Muslim community. The research method used is a qualitative descriptive approach, which involves describing various discussions and identifying Islamic values based on sources from the Quran and Hadith. This method is applied to explore the principles of conversion through case studies of heritage buildings. The findings highlight Islamic values that can be applied in heritage building conversions, providing recommendations for the Muslim community to manage these buildings effectively in accordance with Islamic values while avoiding actions that lead to shirk (associating partners with Allah).